2017
DOI: 10.3390/scipharm85010002
|View full text |Cite
|
Sign up to set email alerts
|

New Synthesis, Structure and Analgesic Properties of Methyl 1-R-4-Methyl-2,2-Dioxo-1H-2λ6,1-Benzothiazine-3-Carboxylates

Abstract: According to the principles of the methodology of bioisosteric replacements a series of methyl 1-R-4-methyl-2,2-dioxo-1H-2λ6,1-benzothiazine-3-carboxylates has been obtained as potential analgesics. In addition, a fundamentally new strategy for the synthesis of compounds of this chemical class involving the introduction of N-alkyl substituent at the final stage in 2,1-benzothiazine nucleus already formed has been proposed. Using nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry and X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The sample was heated in the inert gas atmosphere (argon, 20 mL/min), and the rate of heating was 5 °C/min. The synthesis of the starting methyl 4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxyate ( 1 ) was carried out by the method described in the study [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was heated in the inert gas atmosphere (argon, 20 mL/min), and the rate of heating was 5 °C/min. The synthesis of the starting methyl 4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxyate ( 1 ) was carried out by the method described in the study [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Taking into account the above, it is of interest to study the structure and biological properties of 4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylic acids IX . The main prerequisites for this research were the expressed analgesic activity demonstrated by their synthetic precursors — methyl-4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylates VIII [ 6 ] as well as excellent results obtained during the transition from quinolone esters X , which are similar in terms of their structure, to acids XI [ 7 ] ( Figure 2 ). Another incentive to study the behavior of 4-methyl-substituted benzothiazine esters VIII in alkaline hydrolysis conditions was a simple scientific curiosity: as is known [ 8 ], the corresponding acids cannot be obtained from their 4-hydroxy analogs XII since in the process of their formation, they are immediately decarboxylated to 4-oxo-3,4-dihydro-1 H -2λ 6 ,1-benzothiazin-2,2-diones XIII .…”
Section: Introductionmentioning
confidence: 99%
“… The conventional method for the synthesis of alkyl 1-R-4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylates IX [ 22 , 23 , 24 , 25 ] . …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…This is the method that we used to transform 4-methyl-2,2-dioxo-1 H -2λ 6 ,1-benzothiazine-3-carboxylic acid into an ester. Naturally, the lower alkyl esters of this acid are easier to obtain according to the usual linear scheme [ 22 , 23 ] when the required substituent is introduced at the preliminary stage of the synthesis of the corresponding alkyl (chlorosulfonyl) acetate VII ( Scheme 1 ). It must be remembered that the use of bases at the final stage of the hetericyclization provides an opportunity to avoid easy transesterification [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation